MUSICOGENIC EPILEPSY. A REVIEW OF THE LITERATURE AND A CASE REPORT - V. O. Generalov; T. R. Sadykov; Yu. V. Kazakova; A. M. Yugay; A. B. Orehov (Эпилепсия и пароксизмальные состояния)
Musicogenic epilepsy is a rare form of reflex epilepsy, where seizures are triggered by listening to patient-specific sounds or music. The onset typically occurs in the adult age. In most cases of musicogenic epilepsy, the source of epileptic activity is located in the temporal zone (more on the right) and not associated with structural brain damage as per magnetic resonance imaging. Usually, the seizures have the complex partial nature with automatisms. This report presents a case of a female patient of 53 years old with the onset of epilepsy at an age of 33, with complex partial epileptic seizures provoked by listening to pop music. We detected 2 sources of epileptic activity located in the medial zones of the right and left temporal lobes, with no structural abnormalities of the brain as evidenced by MRI. During a video-EEG examination, listening to a piece of music caused complex partial epileptic seizures with the source of ictal epileptic activity in the medial zones of the left temporal lobe.